Issues, challenges and strategies for doubling the farmers’ income in India – A review - BIHARI, BANKEY; SINGH, MADAN; BISHNOI, RAJESH; MISHRA, P K (The Indian Journal of Agricultural Sciences, 2019)
The Government of India in its annual budget 2016-17 set a policy target of doubling farmers’ income by 2022. Agriculture sustains livelihood for more than half of the India’s total population. Doubling farmers’ income in such a short period is an overwhelming task for decision makers, scientists and policy makers. Doubling farmers’ income is possible through increasing total output and better price realization in market, reduction in production costs, diversification of product, efficient post-harvest management, value addition, etc. In this paper, efforts have been made to detail issues, challenges and strategies to achieve the target of doubling farmer’s income. Specific strategies suggested for achieving the target of doubling farmers’ income were market management, agricultural input management, risk management and agricultural extension strategies.